DEVELOPMENT OF A MODEL OF TRANSPORTATION IN A CONTRAILER - Сілантьєва, Ю. О. (Proceedings of National Aviation University (archive), 2021)
The results of the analysis of the piggyback delivery system and its structural elements are presented. An assessment of the efficiency of the system on the financial costs of transportation and the time of its implementation. A model for calculating the cost of piggyback transportation is proposed, which is sufficiently substantiated and can be used in the improvement of piggyback transportation systems.